Hard and Soft Acids and Bases (HSAB): Investigating Adduct Formation in Non-Aqueous Solvent Media with Selected Divalent Class B Metal Ions in Chemistry - Felicity Uju Onwudinjo (Harati : Journal of Science Education, 2024)
This study explores the Lewis acid/base interactions of divalent metal ions—copper (II), lead (II), and mercury (II)—with Lewis bases 2-naphthol and caffeine in an ethanol solvent. Utilizing the method of continuous variation, absorbance data were analyzed to understand these interactions. Absorbance data analyzed through Job's plot revealed distinct interaction patterns. For the copper (II) system, the Job's plot did not exhibit a maximum, indicating a lack of significant cooperative interaction, with absorbance values fluctuating without a clear pattern. In contrast, the lead (II) and mercury (II) systems demonstrated clear maxima with both 2-naphthol and caffeine, evidencing cooperative interactions. Specifically, the Job's plot for lead (II) with 2-naphthol peaked at an absorbance of 1.25 at a mole ratio of 1:1, and for mercury (II) with caffeine, a maximum absorbance of 1.40 was observed at the same stoichiometry. These results indicate a 1:1 stoichiometry for the adducts formed, suggesting that the interactions of these metal ions with the bases can be described by the Eigen-Wilkins mechanism. This mechanism may thus account for the adduct formation involving the class B Lewis acids studied in a non-aqueous medium, highlighting a distinctive aspect of their chemical behavior.